American disruptor : the scandalous life of Leland Stanford - De Wolk, Roland, 1953- (University of California Press, 2019)
"The life of Leland Stanford reads like a tall tale of the Old West. Born in a country tavern in upstate New York, Stanford followed the Gold Rush to California, became a successful businessman, and invested in railroads. He then made headway into politics, becoming governor of California and later a US senator. As president of the Central Pacific Railroad, Stanford brought the locomotive Jupiter to preside over the completion of the first transcontinental railroad, which led contemporaries to liken him to the namesake Roman god. He then founded one of the most prestigious universities in the world. Stanford lived large and bold, amassing an astonishing fortune, only to die on the brink of bankruptcy. In American Disruptor, Roland De Wolk balances the accomplishments of this quintessential self-made American man with the darker aspects of his life. He shows how Stanford used high public office to steal taxpayer money, only to squander it on mansions, racehorses, jewels, and vast landholdings. Even the eponymous university in Silicon Valley that bears his name, created from the largest private university endowment of all time, was born of tragedy, a memorial to Stanford's fifteen-year-old son who died from typhoid fever. Following his death, his wife struggled to keep the fledgling university afloat, only to be murdered under mysterious circumstances. Although deeply conservative in belief and style, Leland Stanford's life was one of almost unparalleled risk, failure, and reward. Richly detailed and deeply researched, American Disruptor helps restore his rightful place as an architect of modern America"--Provided by publisher.
Keywords: Stanford, Leland, -- 1824-1893.; Stanford, Leland, -- 1824-1893; Governors -- California -- Biography.; Businesspeople -- California -- Biography.; Legislators -- United States -- Biography.; California -- Politics and government -- 1850-1950.; Gouverneurs -- Californie -- Biographies.; Gens d'affaires -- Californie -- Biographies.; Parlementaires -- États-Unis -- Biographies.; Californie -- Politique et gouvernement -- 1850-1950.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; Businesspeople; Governors; Legislators; Politics and government; California; United States; 1850-1950; Biographies